PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THREE-STAGE FISHBOWL DECISION UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDUKSI OKSIDASI DI KELAS X SMA NEGERI 1 PERANAP - Atika Ali Ali; Jimmi Copriady Copriady; Rini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this research is to improve  student achievement on the subject oxidation reduction reaction in class X Senior High School (SMAN) 1 Peranap trough the applying active learning Three-Stage Fishbowl Decision strategy. This research was used Randomized control Group Pretest-Posttest design. The research was conducted from October 2014 to June 2015. The population of the research are all of student in X Senior High School (SMAN) 1 Peranap which consists of 4 classes. Samples of this research have two classes there are class X.4 and X.3 were randomly selected. Class X.4 applied active learning Three-Stage Fishbowl Decision strategy as experiment class and  X.3 as control class. The data analysis technique used homogeneity test is by assessing homogeneous variances of sampel, and hypothesis test (t-test) is by assessing comparison of learning achievement between class. Based on analysis hypothesis test with   d f = 35 + 35 - 2 = 68 (α = 0,05) data obtained arithmetic > table is 4,7376 > 1,67. It showed that active learning Three-Stage Fishbowl Decision strategy can improve student achievement on the subject oxidation reduction reactions class X Senior High School (SMAN) 1 Peranap. Based on normalized gain (N-gain) category increased in experiment class by student achievement was categorized in high (0,71) category, while control class categorized medium (0,51) category. Key Words: Learning Achievement, active learning Three-Stage Fishbowl Decision strategy, and Oxidation Reduction Reaction